Dāstān aur nāvil - Aḫtar, Salīm (Sang-i Mīl Pablīkešanz, 1991)
Critical study of modern Urdu novel and short story writing
In arab. Schrift, Urdu. - Sequel to: Afsānah aur afsānah nigār
Keywords: Urdu; Literatur